A 33% Tuning Range High Output Power V-Band Superharmonic Coupled Quadrature VCO in SiGe Technology - Nasr, Ismail; Dudek, Manuel; Weigel, Robert; Kissinger, Dietmar (IEEE Radio Frequency Integrated Circuits Conference, 2012)
Abstract—This paper presents a wide tuning range superharmonic coupled quadrature Colpitts VCO with high output power. The circuit was fabricated using a low-cost SiGe technology with an ft/fmax of 200/250 GHz. The quadrature VCO employs a novel area efficient coupling technique that uses second harmonic coupling. Downcoversion mixers are implemented to provide an intermediate frequency signal, enabling easier measurement. A phase imbalance below 2 degrees is measured between the quadrature outputs, over a 6 GHz tuning range. The quadrature VCO can be tuned between 55 and 76.5 GHz having a record tuning range of approx. 33%. Moreover, the quadrature VCO has a maximum measured output power of +10.5dBm, and a minimum phase noise of -97 dBc/Hz. The overall chip draws 303mA from a 3.3V supply.
elib2cris::1512001600,nasr2012a
Keywords: Quadrature oscillator (QVCO); Colpitts; Wide tuning range; superharmonic coupling

Advanced Millimeter-Wave FMCW Radar System Simulations for Automotive Applications - Weigel, Robert; Dudek, Manuel (Electrical and Electronic Engineering for Communication Workshop - Entwicklerforum - Fachmesse, 2011)
elib2cris::1512001600,weigel2011b

A millimeter-wave FMCW radar system simulator for automotive applications including nonlinear component models - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (European Radar Conference (EuRAD), 2011)
A fully differential millimeter wave frequency modulated continuous wave (FMCW) radar architecture is built up in Agilent's RF design and system simulation environment ADS® to investigate the influence of RF impairments on system level on the target signal. To take also the surroundings of the automotive scenario into account a 3D ray tracing channel simulator is coupled in a Matlab® co-simulation providing realistic data of the traffic situation. Therefore investigations on the performance of the radar frontend in an automotive long range radar (LRR) application are enabled, the functionality of the circuitry can be verified and components designed in the most beneficial way, so that the best performance is achieved with the available resources. For nonlinear behavior the frontend components are parameterized according to recently published values for 77GHz SiGe circuits. The functionality of the complete simulation environment is demonstrated by calculating a typical traffic situation.
elib2cris::1512001600,dudek2011c

An Advanced Millimeter-Wave FMCW-Radar System Simulation Environment for the Automotive Sector - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (12. GMM/ITG-Fachtagung ANALOG, 2011)
In this paper a millimeter-wave radar system simulation environment for frequency-modulated continuous-wave radar using a 3D ray tracing channel simulator is presented. Therefore we use Agilent’s RF design environment ADS® for system simulation and calculate the channel impulse response based on the data received from a 3D ray tracer in a Matlab® co-simulation. To reduce computing time the whole signal flow is processed in a complex baseband representation and scattering center models are used as substitute for complex polygon targets as further improvement. Nevertheless all effects occurring at harmonic bands due to nonlinearities in the transmitter and receiver circuits are well reflected in the simulation. A typical road scenario is simulated and the results show the capabilities of the simulation approach in terms of speed and accuracy.
elib2cris::1512001600,dudek2011e

A Versatile System Simulation Environment for Millimeter-Wave Phased-Array FMCW-Radar Sensors for Automotive Applications - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference (APMC), 2011)
In this contribution a versatile system simulation environment for radar sensors being developed to operate in the automotive area is introduced. It combines a frontend simulation engine that is coupled in a co-simulation with a 3D ray-tracing tool to take the effects of the automotive radar channel into account, thus providing accurate and reliable results concerning the behavior of the implemented circuits in certain traffic situations. With respect to the latest developments in automotive radar, i.e. the transition from former comfort systems to current systems including an increased number of safety functions, the system simulation environment has been extended to support investigations on the phased-array radar principle. Applying this technique in the automotive area promises advantages in target detection in the vehicles vicinity by the means of increased hardware requirements, resulting in radar systems that are by far more difficult to design due to the number of side-effects that have to be additionally considered during the development process. To demonstrate the capability of this advanced simulation approach a typical traffic scenario is calculated showing not only the advantages of phased-array radar for the automotive field but also the performance of the simulation environment built up.
elib2cris::1512001600,dudek2011f

Consideration of higher frequency bands in accurate millimeter-wave FMCW-radar system simulations for automotive applications - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (Wireless and Microwave Technology Conference, 2011)
In this paper we demonstrate the necessity of taking harmonic bands into account when performing accurate simulations for millimeter-wave frequency-modulated continuous-wave (FMCW) radar systems. Especially under nonlinear conditions when harmonics are generated and influence the signal quality of target detection the higher frequency bands cannot be neglected anymore. In ordinary complex baseband simulations, that are considered as a means to keep the amount of data low in FMCW radar simulations, previous knowledge is needed to explicitly model the impact of effects in higher frequency bands on the specific circuit. Our approach takes the effects of multiples of the actual operating frequency into account, thus enabling higher accuracy while keeping the amount of data moderate. As an example for the capability of this simulation approach a scenario is calculated showing the difference between both simulation strategies.
elib2cris::1512001600,dudek2011a

Eine erweiterte Millimeterwellen FMCW-Radar Systemsimulationsumgebung fuer den Einsatz im Automobilbereich - Dudek, Manuel; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (ANALOG'11 Fachtagung Entwicklung von Analogschaltungen mit CAE-Methoden, 2011)
In diesem Artikel stellen wir eine Simulationsumgebung fuer Millimeterwellen FMCW-Radare fuer den Einsatz im Automobilbereich vor, die einen 3D-Kanalsimulator beinhaltet. Dafuer nutzen wir Agilent's RF Entwicklungsumgebung ADS(R) fuer die Systemsimulation und berechnen die Impulsantwort des Kanals, basierend auf den Daten die von einem 3D-Raytracer generiert werden, in einer Matlab(R) Cosimulation. Um die Rechenzeit zu reduzieren findet der gesamte Signalfluss im komplexen Basisband statt und aufwaendige Polygonmodelle werden durch ihre Streuzentrenmodelle als weitere Verbesserung substituiert. Alle Effekte in den Harmonischen Zonen, die auf Grund von Nichtlinearitaeten im Sende- oder Empfangsmodul auftreten, werden in der Simulation korrekt wiedergegeben. Um die Leistungsfähigkeit des Simulationsansatzes, was Geschwindigkeit und Genauigkeit anbelangt, zu evaluieren, wird ein typisches Verkehrsszenario simuliert.
elib2cris::1512001600,dudek2011d

Millimeter Wave FMCW Radar System Simulations including a 3D Ray Tracing Channel Simulator - Dudek, Manuel; Wahl, René; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference (APMC), 2010)
In this paper a millimeter-wave radar system simulation environment for frequency-modulated continuous-wave (FMCW) radar using a 3D ray tracing channel simulator is presented. Therefore we use Agilents' RF design environment ADS® for system simulation and calculate the channel impulse response based on the data received from a 3D ray tracer in a Matlab® co-simulation. To reduce computing time the whole signal flow is processed in a complex baseband representation and scattering center models are used as substitute for complex polygon targets as further improvement. Nevertheless all effects occurring at harmonic bands and at DC due to nonlinearities in the transmitter and receiver circuits are well reflected in the simulation. A typical road scenario is simulated and the results show the capabilities of the simulation technique in terms of speed and accuracy.
elib2cris::1512001600,dudek2010a
Keywords: Computational modeling; CW radar; FM radar; radar computing; ray tracing; road vehicle radar; millimeter wave radar; 3D ray tracing channel simulator; Matlab cosimulation; channel impulse response calculation; complex polygon target; frequency-modulated continuous-wave radar; millimeter-wave radar system simulation; scattering center model; RF impairments

System Analysis of a Phased-Array Radar Applying Adaptive Beam-Control for Future Automotive Safety Applications - Dudek, Manuel; Nasr, Ismail; Bozsik, Gabor Josef; Hamouda, Mohammed; Kissinger, Dietmar; Fischer, Georg (IEEE Transactions on Vehicular Technology, 2015)
elib2cris::1512001600,dudek2015

The Impact of Antenna Characteristics on Target Signal Detection in FMCW-Radar System Simulations for Automotive Applications - Dudek, Manuel; Nasr, Ismail; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (IEEE Radio Wireless Symposium (RWS), 2012)
In this scientific paper a versatile system simulation environment is introduced that enables investigations on millimeter-wave FMCW-radar sensors. With respect to the latest developments in automotive radar the simulator combines an RF-frontend simulation engine and a 3D ray-tracing tool to take the effects of the radar channel into account. Furthermore different antenna characteristics can be generated by the phased-array radar topology implemented to examine not only the behavior of the RF-frontend but the impact of the concrete traffic situation on the whole sensor system. Therefore development engineers are actively assisted with their task to design new accurate and reliable systems, thus enabling the transition from current pure comfort systems to future systems including an increased number of safety functions. To demon-strate the usability of this advanced simulation approach for the development of future radar sensors a typical traffic scenario is calculated showing not only the impact of the antennas’ beamwidth and side-lobes on target signal detection, but also the performance of the simulation environment built-up.
elib2cris::1512001600,dudek2012

The Impact of Phase Noise Parameters on Target Signal Detection in FMCW-Radar System Simulations for Automotive Applications - Dudek, Manuel; Nasr, Ismail; Kissinger, Dietmar; Weigel, Robert; Fischer, Georg (CIE International Conference on Radar, 2011)
Accurate system simulations have proven to be a valuable aid during the development process and help to decrease the time-to-market and the amount of design iterations, thus keeping development costs at a moderate level. Therefore a frequency-modulated continuous-wave (FMCW) radar system simulation environment has been built up, enabling for performance analysis of millimeter-wave radar frontends for automotive applications. A key parameter especially for radar systems applying the FMCW principle thereby is the linearity of the frequency ramp as it directly affects the quality of the target signal and thus the performance of the entire radar sensor. Hence in this scientific paper we investigate the influence of a phase noise afflicted VCO on the target signal detection, and the range resolution respectively. Leeson’s equation is applied to model oscillator phase noise and the results show which parameters are crucial for the radar system. Eventually a two-target scenario is calculated to substantiate the statements taken.
elib2cris::1512001600,dudek2011b

Towards Future Automotive Safety Applications based on Phased Array FMCW-Radar Sensors – a Holistic Simulative Approach Incorporating RF-Frontend Impairments - Dudek, Manuel (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)